Assessing current and future changes in extreme climate events in Brazil - Ávila Díaz, Álvaro Javier (2020)
Brazil is vulnerable to climatic variability, especially those related to climate extremes of the air temperature and precipitation because they provide expressive losses related to agricultural activities and the management of water resources. Climate change is expected to have a likely negative socio-economic impact, increasing the number of natural disasters in regions where climate change will be more pronounced. The main objective of this study was to evaluate the current and future changes of the climatic extremes in Brazil. To understand the magnitude of these changes, extremes of temperature and precipitation set by the team of experts from the climate extremes indices defined by the Expert Team on Climate Change Detection and Indices (ETCCDI) were selected. The first part of the research evaluated the performance of 25 Earth System Models (ESMs) in representing the variability of climatic extremes for the period between 1980 and 2005. ESMs use statistical and dynamic downscaling to reduce the original horizontal scale, which ranges from 1-3o for a spatial resolution of 0.25 ° (~ 25 km latitude/longitude). Statistical downscaling data were obtained from the National Aeronautics and Space Administration Earth Exchange Global Daily Downscaled Projections (NEX- GDDP). Dynamic downscaling data was provided by the National Institute for Space Research (INPE). The results showed that the obtained indices, using ESM downscaling, were similar to the observed climate indices, although the performance metrics revealed that climate extremes are not adequately represented in the Amazon basin. In addition, there are uncertainties in heat wave simulations for almost all models. In general, the average of the set of simulations of the ESMs, or multi-model ensemble (MME), that used statistical downscaling has the best results in comparison to any individual model. The second part of the work, aimed to assess the trend and magnitude of climate extremes in the last four decades (1980-2016) using several databases (e.g., observations and reanalysis). The projected changes in the extreme indices up to the middle of the 21st century (2046-2065) and the end of the 21st century (2081–2100) in relation to the 1986-2005 reference period were also analyzed. Future climate changes were analyzed from the ensemble of 20 downscaled ESMs of the NEX-GDDP dataset. For the historical period (1980-2016), temperature-related indices showed consistent heating patterns across Brazil with increasing trends on hot days/nights and decreasing trends for cold days/nights. Also, a similar warming pattern is projetected for the mid and late 21st century. For precipitation-related indices, observations show an increase in consecutive dry days and a reduction in consecutive wet days in almost all of Brazil from 1980-2016. Additionally, future scenarios indicate that the frequency and intensity of extremely wet days are likely to be more intense. The results of this research aim to contribute to the current understanding of extreme weather events in Brazil, in order to provide further essential insights for studies of impact, adaptation and vulnerability to climate change. Keywords: Extreme climate indices. Hydrological Basins. Climate Change. Trends. CMIP5. Downscaling.